Humanizing the inhabited designing an informally inhabited bridge space into a mixed-use habitable bridge - Servando, Sophia Ysabelle H.; Alex Ray Evangelista (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
A habitable bridge is an innovative architectural typology with a rich global history. While often regarded as visionary, it presents a promising solution to contemporary urban challenges such as land scarcity and housing and public space shortages. And while this typology is yet to be actuated in real life in the Philippines, this study explores how the redesigning of bridge spaces into a multi-use habitable bridge can become a modern-day solution to existing urban problems in the Philippines through the introduction of innovative building typologies to our cities dense urban landscape. This research highlights the potential of habitable bridges as a means of increasing the utility of underused interstitial spaces such as bridges. It aims to produce a habitable bridge in consideration of the Philippine context with regards to its concerns of land scarcity and the persistent unsafe habitation of bridge spaces in urban areas. The development aims to address this gap in architecture as well as provide more public recreational spaces for the residents of Manila, specifically the Ermita and Sta. Cruz area by creating a mixed-use space that takes advantage of the scenic views of the Pasig River.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Mixed-use developments -- Metro Manila; Visionary architecture -- Metro Manila; Habitable bridges; City planning -- Metro Manila